2011
DOI: 10.1002/j.1556-6678.2011.tb00076.x
|View full text |Cite
|
Sign up to set email alerts
|

Counselors', Rehabilitation Providers', and Teachers' Perceptions of Mental and Physical Disabilities

Abstract: The diversity perceptions of human service professionals may be critical indicators of effective service provision. Specifically, this study explored the disability perceptions of counselors, rehabilitation providers, and teachers (N = 172) enrolled in a large, southeastern university. A 76% response rate was achieved in the study, indicating clear differences by human service providers' preparation area and perceptions of disability type. Implications for preparation and future research are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
(30 reference statements)
1
1
0
Order By: Relevance
“…Strike et al (2004) found that mental health professionals' cumulative personal/interpersonal-, work-, and training-related experiences yielded higher levels of disability competence compared with that of their less experienced counterparts. This finding aligns with attitudinal research, which indicates that more positive attitudes toward IWDs are associated with higher levels of self-perceived disability competence (Hollimon, 2007) and linked to areas of academic/professional specialization (Carney & Cobia, 1994;Thomas et al, 2011).…”
supporting
confidence: 86%
“…Strike et al (2004) found that mental health professionals' cumulative personal/interpersonal-, work-, and training-related experiences yielded higher levels of disability competence compared with that of their less experienced counterparts. This finding aligns with attitudinal research, which indicates that more positive attitudes toward IWDs are associated with higher levels of self-perceived disability competence (Hollimon, 2007) and linked to areas of academic/professional specialization (Carney & Cobia, 1994;Thomas et al, 2011).…”
supporting
confidence: 86%
“…Due in part to lack of exposure, some teachers have low or no expectations that learners with educational barriers can or will participate in classroom interaction and learning, which consequently results in the focus of their school day becoming caring and nurturing rather than instruction and inclusion (Bornman, Alant, & Uys, 2008). Teachers who have gained experience with learners with barriers to learning, on the other hand, tend to feel more self-efficacious about their ability to effectively educate such learners in a mainstream classroom (Avramidis & Kalyva, 2007;Thomas, Curtis, & Shippen, 2011). In a survey of teachers in Botswana who had not previously worked in inclusive settings, those who had a friend or family member with a disability evidenced significantly fewer concerns about including learners with barriers to learning in their classes (Chhabra et al, 2010), suggesting that mere exposure to people with disabilities may facilitate more positive attitudes regarding inclusion.…”
Section: Teachers' Attitudes About Learners With Barriers To Learningmentioning
confidence: 99%